2019
DOI: 10.5944/openpraxis.11.1.932
|View full text |Cite
|
Sign up to set email alerts
|

But What Do The Students Think: Results of the CUNY Cross-Campus Zero-Textbook Cost Student Survey

Abstract: The results of the first cross-campus survey of student opinions on Zero Textbook Cost (ZTC) courses are in: City University of New York (CUNY) students like their ZTC courses, primarily for the cost savings and ease of access. The survey results yield rich data about how positively students feel about their Zero Textbook Cost (ZTC) courses as well as ways to improve the design and delivery of Zero Textbook Cost courses to make them more beneficial for student learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 3 publications
1
29
0
Order By: Relevance
“…Unfortunately, this practice has been shown to have an impact on the student experience in the current higher education context. This is due to the high cost of textbooks, which can potentially prove to be an access barrier to essential educational resources (Brandle et al, 2019). In fact, as of 2017, the U.S. Bureau of Labor Statistics reported that the cost of textbooks rose by 142% over the last decade and a half, which represents a rate that is four times that of inflation (U.S. Bureau of Labor Statistics, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, this practice has been shown to have an impact on the student experience in the current higher education context. This is due to the high cost of textbooks, which can potentially prove to be an access barrier to essential educational resources (Brandle et al, 2019). In fact, as of 2017, the U.S. Bureau of Labor Statistics reported that the cost of textbooks rose by 142% over the last decade and a half, which represents a rate that is four times that of inflation (U.S. Bureau of Labor Statistics, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…2. For analysis of OER from students' perspectives, see Brandle et al (2019) and Jaggars, Folk, and Mullins (2018). For analysis of faculty opinions of OER, see Allen and Seaman (2014).…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Examining student perceptions of textbook cost is a relatively new endeavor in this area, and much of the focus is on comparing the quality or efficacy of traditional textbooks to OER. There are a handful of studies that explore student perceptions of impact of the cost of course materials on their quality of life; how cost impacts student success; and how students describe their engagement with course materials (Brandle et al, 2019;Martin, Belikov, Hilton, Wiley & Fischer, 2017;Stein, Hart, Keaney & White, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…City University of New York (CUNY) developed a zero textbook program and conducted a survey (N=890) to determine student perceptions of the program (Brandle et al, 2019). Fifty-five percent of participants indicated that the top benefit of the zero textbook program was cost savings.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation